GAME-BASED BACKHAND TENNIS TECHNIQUE LEARNING MODEL TO IMPROVE LEARNING OUTCOMES - Dio Alif Airlangga Daulay; Iman Sulaiman; Fatah Nurdin (Gladi : Jurnal Ilmu Keolahragaan, 2021)
The purpose of this study is to find out a learning model using a game-based tennis backhand skill model. The method used is Research & Development with mixed methods research approach that combines qualitative and quantitative methods. It is intended to be able to reach or process all data or information so that a comprehensive explanation will be obtained. The number of samples as many as 20 respondents. The steps taken in the trial include: (1) establishing a group of research subjects (2) Carrying out Pretest (3) trying the model that has been developed (4) carrying out post-test (5) looking for the average score of pretest and posttest and compared between the two (6) looking for the differences between the two averages through statistical methods (t-test) to find out whether or not there is a significant influence of the use of the model. The conclusion of this study is that game-based tennis backhand learning model can be developed and applied in the process of learning backhand techniques of tennis effectively and efficiently.